Reconstruction of Paleo depth and Paleo temperature from C- O stable isotope records of Mishrif Formation, southern Iraq - Taha, Taher M.; Abdullah, Enaam J. (Iraqi Journal of Science, 2019)
Stable isotopes 18O/16O and 13C/12C in the carbonate rocks of the Mishrif Formation are examined here to define the depositional characters in the basin includes paleo temperatures and paleo depth. The Mishrif formation (Cenomanian – Early Turonian) has extensive distribution in Iraq and Middle East. Mishrif Formation composed of organic detrital limestone. Four boreholes in four oilfields, Noor – well (11), Amarah – well (14), Buzurgan – well (24), Halfaya – well (8), in south east of Iraq have been studied.The studied samples have negative δ18O isotope values studied well, with Average (-4.11‰), (-4.47‰), (-4.48‰), (-4.18‰) in the studied wells respectively. Carbon Isotope composition positive values in the study samples, with average (2.32‰), (1.84‰), (2.20‰), (2.24‰) are studied well respectively. The Stable isotope (18O/16O and 13C/12C) of Mishrif Formation provide the first records of paleotemperature for the (Cenomanian – Early turanian ) which indicate moderate during deposition. The plot of depositional environment refers to warm water carbonate sediment and the bulk samples cluster tightly to small positive reflect modal isotope composition of dominant skeletal marine carbonate. The paleo-salinity (Z values) provide the marine deposits in studied samples. As the paleo-temperature was high temperature by (T values). The paleo depth he all studied samples in the four oilfields are fall in the same level which is in the upper part of Thermocline this indicate the moderate depth